Artificial insemination in camelidae - A.E.B. Zeidan (Tropical and Subtropical Agroecosystems, 2007)
The most important problems of ArtificialInsemination (AI) in Camelidae is its timing inrelation to ovulation in the she-camel. The presentarticle reviewed collection of semen, processing ofsemen, manipulation of the female and semendeposition technique in Camelidae species.Commonly, semen is collected by electroejaculation,artificial vagina (AV), flushing of the epididymus withsaline solution, while the more accepted methods arethe former two methods. Semen is usually used in rawcondition or after extension, depending on the methodof semen processing. In the fresh raw method, wholesemen is used within minutes or after few hours.Extension of the semen ejaculate is carried out byadding extenders and it is required in more efficientuse of AI, in short-term preservation or liquid semen(within a few hours or days) and long-termpreservation or frozen semen (months or years). Inshort-term preservation, semen is used extended underdifferent temperatures (30, 25 or 4oC). Long-termpreservation is carried out by cryopreservation.Packaging methods such as pellets, ampoules or inplastic straws with different volumes (0.25, 0.5 or 4ml) represent different freezing procedures. Thequality and survival of spermatozoa of post-thawsemen are highly variable from one male to the other,even after using the same freezing technique. Toensure that the inseminated females ovulate, hormonalmanipulation of ovarian activity is used such as theinduction of follicular activity and ovulation, as wellas, synchronization of these phases in a group offemales. The best time for insemination can only bedetermined by ultrasonography and/or rectal palpationof the ovaries. The other alternative is to inseminate atknown intervals following induction of ovulation byhormonal treatment with human-chorionicgonadotropin (hCG) or gonadotropin-releasinghormone (Gn-RH).